Avaliação de biomarcadores bioquímicos no peixe estuarino Micropogonias furnieri exposto agudamente ao anti-incrustante clorotalonil - TORRES , Thamires Alexsandra (2019)
The development of activities in the coastal regions has impacted aquatic ecosystems more and more, causing changes in water quality through the continuous release of chemical compounds, such as the biocides used in antifouling paints and agrochemicals. The concern regarding these compounds is that most of them do not reach only the target organism, resulting in biological alterations in other aquatic organisms as well. The evaluation of potential effects caused by the contaminants in aquatic biota can be performed through ecotoxicological tests. However, more conservative tools such as biomarker analyzes represent more efficient responses in studies that aim an early diagnosis of biota impacts. Thus, in this study, assessments of the following biochemical responses were performed, such as acetylcholinesterase (AChE), glutathione-S-transferase (GST), etoxiresorufina-desetilase (EROD) and lipoperoxidation (LPO), in specific tissues of the estuarine fish Micropogonias furnieri exposed to the biocide anti-fouling chlorothalonil (C8Cl4N2). In order to do, the organisms were exposed via intraperitoneal to two concentrations of chlorothalonil (C1 - 0,35 μg/g and C2 - 3,5 μg/g) in addition to a control group (C). The enzymatic activity of AChE was measured in the brain and muscle, the GST was in the liver and gill, and the LPO was in the muscle, gill, and liver (96h after application). The results showed that the activity of GST in the liver did not present significative difference between the experimental groups (C, C1 and C2), which may be related to a possible depletion of GHS levels and consequent inhibition of GST due to excessive accumulation of chlorothalonil in this organ. In the other hand, in the gills, there was an increase in enzymatic activity in the group exposed to a higher concentration of chlorothalonil (C2) which may be related to an increase of GSH levels for chlorothalonil detoxification in the gills. LPO in the liver and muscle did not presente significative diferences, possibly due to the efficiency of the antioxidant defenses, with no alterations. However, in the gills was a decrease in LPO (C2), corroborating with the results of GST that was higher in C2. Concerning AChE, it is noticed that there is an increase of the activity in the brain and muscle, wich may be related to a compensation mechanism due to stress in the organism. Thus, it was observed that the compound causes biochemical variations mainly in parameters related to the process of biotransformation and neurotoxic responses in M. furnieri.